"You Cannot Serve God and Mammon": Economic Relations and Human Flourishing in Luke. (1st March 2013) - Pickett, Raymond
<x xml:space="preserve">Abstract</x> Abstract: Economics is essentially a matter of value, and capitalism is a system of value creation in which the individual is valued at the expense of the community and the cosmos. In contrast to this, Luke tells the story of Jesus as a vision of salvation that is covenantal and communal, encompassing every dimension of life, including the economic. God and mammon represent two antithetical wellsprings of value and desire that orient intentions and actions in different directions. Mammon represents the realm of self‐justification, self‐reliance, self‐aggrandizement, and in our own disenchanted world the "buffered" and disengaged self, while God represents the domain of human flourishing characterized by interdependence and sharing.